Urinary N-acetyl-beta-d-glucosaminidase (NAG) with neutrophil gelatinase-associated lipocalin (NGAL) improves the diagnostic value for proximal tubule damage in diabetic kidney disease - Siddiqui, Khalid (3 Biotech, 2019)
Screening for diabetic kidney disease (DKD) remains a challenge; however, there has been an ongoing research to investigate the diagnostic value of different biomarkers to identify DKD. The aim of this study was to assess the diagnostic value of both N-acetyl-beta-d-glucosaminidase (NAG) and neutrophil gelatinase-associated lipocalin (NGAL) in the progression of DKD. This cross-sectional case–control study included 92 type 2 diabetic patients with or without DKD. Urinary NAG and NGAL were measured to evaluate their diagnostic values as biochemical markers related to DKD. Both urinary NAG and NGAL levels were significantly higher among patients with DKD. In multiple linear regression analysis, NAG showed a positive significant association with NGAL in the three different adjusted models, while no significant correlation with fasting blood glucose, glycated hemoglobin, serum creatinine, estimated glomerular filtration rate, and albumin creatinine ratio were observed. The area under the curve for NGAL was 0.659 (p = 0.01) and 0.564 (p = 0.297) for NAG in DKD patients. This study demonstrates the association between urinary NAG and NGAL as a tubular damage marker for DKD although longitudinal studies are needed to evaluate its diagnostic value.